Exil und Identität : Die italienischen Juden in der Schweiz (1943-1945) - Longhi, Silvano (2017)
Once Germany invaded Italy in September 1943, the Jews of Italy became part of the Final Solution. The author examines a brief but important phase of their history by looking at the fate of those Jews who were able save themselves in Switzerland. They became actively engaged in politics, education, and journalism while also providing support to the partisan struggle and to the Jews who remained in occupied Italy.